Evaluation of breastfeeding promotion, support, and knowledge of benefits on breastfeeding outcomes - Kornides, Melanie (2013)
We examined how prenatal exposure to breastfeeding information from various media sources, maternal knowledge of benefits, family and clinician support, and peer practices influence breastfeeding outcomes in early infancy. Initiation of breastfeeding, any breastfeeding at two months, and exclusivity of breastfeeding at two months were examined in a cohort of US women using data from the Infant Feeding Practices Study II. Descriptive statistics, chi-square analyses and logistic regression were conducted. Approximately 85 percent of the women initiated breastfeeding. At two months, 63.8 percent continued breastfeeding, while only 38.1 percent breastfed exclusively. Mothers with greater knowledge about breastfeeding benefits were 11.20 (95%CI: 6.87–18.45) times more likely to initiate breastfeeding and 5.62 (95% CI: 4.19–7.54) times more likely to breastfeed at two months than those with lower levels of knowledge. Women whose families prenatally supported exclusive breastfeeding were 8.21(5.12–13.2) times more likely to initiate and continue breastfeeding (OR 3.21, 95%CI: 2.51–4.11). Clinicians who supported breastfeeding only also increased the odds of a woman initiating breastfeeding (OR 1.95, 95% CI: 1.31–2.88). Interventions to increase maternal knowledge of breastfeeding benefits and family and clinician support of breastfeeding in the prenatal period may help increase breastfeeding rates. The encouragement of breastfeeding needs to be a priority among health care providers to improve the health of mothers and infants.